PERAN KOMUNIKASI DALAM PROSES BIMBINGAN DAN KONSELING - Frista Fitriany Ramadhanita; Nur Safitri; Ida Ayu Putu Anggie Sinthiya (Jurnal Bimbingan Penyuluhan Islam, 2022)
This paper is to find out the process of Guidance and Counseling which is a process of scientific and professional psychological and humanitarian assistance provided by the counselor (counselor) to the guided (client), so that they can develop optimally, namely being able to understand themselves, direct themselves, and actualize themselves. , according to the stage of development, characteristics, potential possessed and the background of life and the environment so that happiness is achieved in life. In the implementation of guidance and counseling, good and polite communication techniques and skills are needed so that they can open their hearts, thoughts and feelings voluntarily and sincerely following the flow of conversation so that in the end the client really feels guided by the counselor himself. The method used in this research is a literature study